Development and Evaluation of Experiential Learning with Digital Simulation (ELDS) Modules in Electricity & Magnetism - Monaliza A. Suba; Ernesto F. Manlapig Jr. (Journal of Research in Education and Pedagogy, 2025)
The extreme heat index experienced in the Philippines, which forced several schools to transition to distance learning, highlights the urgent need for instructional materials suitable for remote education. This study aimed to develop and evaluate Evaluation of Experiential Learning with Digital Simulation (ELDS) modules in electricity and magnetism as potential instructional resources for General Physics 2 class. The participants included in the study involved physics experts (n = 5) and Grade 12 STEM students (n = 43) from a private school in Bulacan, Philippines. A Research and Development (R&D) approach utilizing the ADDIE framework was employed, as the study focused on designing and developing instructional materials for the physics subject. Quantitative data were collected using the ELDS Module Evaluation Checklist (ELDSMEC) and analyzed through average means, standard deviations, p-values, and the Mann-Whitney U test. The results indicated no significant difference (p > 0.05) between the assessments of physics experts and STEM students regarding the potential effectiveness of the ELDS modules in electricity and magnetism. This suggests that both groups recognize the developed modules as valuable tools for enhancing student learning in these critical areas of physics. The findings underscore the importance of creating adaptable and effective instructional materials that can support distance learning, particularly in response to environmental challenges such as extreme heat index.